Disparities in neonatal abstinence syndrome and health insurance status: A statewide study using non–claims real‐time surveillance data. Issue 3 (27th October 2020) - Umer, Amna; Lilly, Christa; Hamilton, Candice; Breyel, Janine; Allen, Lindsay; Rompala, Ancilla; Moore, Carrie; O'Dierno, Patricia; John, Collin
Abstract: Background: Most studies examining the relationship between neonatal abstinence syndrome (NAS) and health insurance status in the United States (USA) have used administrative insurance claims data, which is subject to myriad limitations. We examined the association between NAS and health insurance status in a large geographically defined rural population in the United States, using non–claims data. Methods: We utilized data from a population‐based cohort of all newborns born in 2017–2019 in the rural state of West Virginia (WV) and restricted analyses to WV residents' births (n = 46 213). NAS was defined as neonatal withdrawal from many substances, including opiates and not limited to those cases that require pharmacological treatment. Results: Medicaid covered more than half (52.6%) of all infants' births in the state of WV. The incidence of NAS was 85.8 and 12.7 per 1000 livebirths in the Medicaid and privately insured groups, respectively. Among all infants diagnosed with NAS, 86.1% were enrolled in the state's Medicaid programme. The risk of NAS in the Medicaid‐insured newborns was higher than privately insured newborns in the unadjusted analysis (risk ratio (RR) 6.76, 95% confidence interval (CI) 5.95, 7.68) and the adjusted analysis RR 3.00, 95% CI 2.01, 4.49); adjusted risk difference 20.3 (95% CI 17.5, 23.1 cases per 1000 livebirths). Conclusions: NAS is an important indicator of the immediate effect of the opioid crisis. This study shows the disparity in NAS by health insurance status for a large rural population in the United States, and its burden on the state's Medicaid programme. Providing timely and accurate estimates of NAS is important for public health policies and decision making.